أصل الکرد - خورشید, فۆاد حمە; طالب, جەزا تۆفیق (Sulaimani Journal for Humanities, 2003)
This study is dealing with the primitive and ancient origin of Kurds. To achieving that goal this study is referring to the geographical and environmental factors and phenomena, undoubtedly such factors has a great influence on the development of Kurdish civilization and its stages that took shape in the mountainous region of Zagros. The subsequent stages of Kurdish civilization could be studied within the framework of historical, civilized and archaeological information, those stages began with the end of the latest Pleistocene ice age, which began nearly 100.000 years ago, the study covers this long peripd until (550 BC), the end of Median Era, during which the Kurds had completed their ethnic and national characters. This study also deals with the essential features of "Gottes", their, their headquarters, their civilization and their homeland. The study also deals with the subsequent civilization such as Mousterian, Bradostian, and that belongs to zer- zeh cave, in one hand and on other hand the study explains the stage of food production, and the exploring of agriculture, the study too, explain the Median Era in detail, and it mentions to their origin and how they extend their power and shaped the origin of Kurds. In the end of the study we reached to some useful conclusions.